Fighting for your marriage positive steps for preventing divorce and preserving a lasting love - Markman, Howard 1950-; Stanley, Scott 1955-.; Blumberg, Susan L. 1959-. (San Francisco Jossey-Bass, 2001)
Explains the PREP (Prevention and Relationship Enhancement Program) approach to improving a marriage.
Understanding the risks on the road to lasting love -- Four hallmarks of a great relationship: PREP in a nutshell. Destructive patterns : signs of danger ahead. Changing roles, changing rules : men and women in conflict -- Teaming up to handle conflict. When what you heard isn't what I said : understanding filters in communication. Talking safely without fighting : the speaker-listener technique. Controlling the home fires : handling issues and events well. New perspectives on problems and problem solving. Keeping conflict under control : ground rules for a great relationship -- Enjoying each other. Safe harbor : preserving and protecting friendship. Playing together : how to succeed in fun without really trying. Sense and sensuality : enhancing and protecting your sex life. Core beliefs and spiritual intimacy -- Staying the course. Why you can't always get what you want : unraveling the mysteries of expectations. Forgiveness : restoring hope. Sticking, stuck, or stopped : on the path to commitment. What to do now -- Some thoughts on domestic violence.
Includes bibliographical references (p. 357-364) and index.
Keywords: Marriage; Interpersonal relations; Interpersonal communication